Grammatical awareness among primary school english language teachers - Munir Shuib, (Penerbitan UKM, 2009)
This paper reports a study of Malaysian primary school teachers’ grammatical awareness. In particular, the study seeks to examine the English language teachers’ nature and level of grammatical awareness. Questionnaire and interview techniques were used to elicit data from primary school teachers who were following their B. Ed TESOL programme in Universiti Sains Malaysia in 2006 and 2007. Findings of the study shed light on an important facet of primary school English language teachers’ metalinguistic awareness in Malaysia, and informs the improvement of teacher education in the country